(untitled) (Interdisciplinary Studies Journal, 2025)
This study investigates the identity and sense of belonging of young people of Lebanese descent in Brazil, an ethnically neglected group in academic research. Lebanese immigration in the early 20th century brought a rich cultural heritage; however, its influence on the identity formation of descendants is still little explored. The aim of this study is to analyze how ancestry and cultural norms affect the identity construction of young Syrian-Lebanese, highlighting the importance of their representation in contemporary Brazilian society. The research was conducted through qualitative interviews with six young people of Lebanese descent from various cities in Brazil. The interviews were analyzed using content analysis methodology, identifying and categorizing emerging thematic axes. The results revealed that ancestry plays a crucial role in the identity formation of these young people. Cultural norms influence their adaptation to the Brazilian context, generating conflicts between family traditions and local culture, while the lack of representation and knowledge about Lebanese immigration contributes to the marginalization of their experiences. This study emphasizes the relevance of understanding the experiences of young people of Syrian-Lebanese descent in Brazil, recognizing that ancestry impacts identity construction and social integration. The research highlights the need for greater representation in discussions on cultural diversity, contributing to a broader understanding of youth experiences in multicultural contexts.